O PONTO DE PARTIDA DO ARGUMENTO CONTRATUALISTA: DO ESTADO DE NATUREZA DE HOBBES AO ARTIFÍCIO DA POSIÇÃO ORIGINAL DE RAWLS - Delmo Mattos (Princípios, 2014)
This article aims to address the nature of the contractarian argument in Hobbes and Rawls. For both, it becomes clear the two basic elements present in both political theoretical argument, ie, the state of nature and the original position. The relationship of these two elements provides a substantial view of philosophical and political project aimed at each one as their conceptual similarities and discrepancies. To highlight this issue, there is discerned in an argumentative way that relates both those basic elements of the theoretical argument, and the feasibility of applying a starting point as the foundation of political argument.